Estimasi Manfaat Ekonomi Objek Wisata Museum Geologi, Bandung, Jawa Barat, Indonesia: Aplikasi Travel Cost Method - Andrian Dwiky Lasmana (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
The Geology Museum is one of the most famous education-based tourist attractions in the city of Bandung. The purpose of this research is to calculate the economic benefits of the museum using the Individual Travel Cost Method. The data were obtained through a survey of visitors with a total of 51 observations. Only 36 observations could be used because the other 15 give incomplete and unclear data. There are 6 variables used, namely visit frequency as the dependent variable and travel costs, income, education, age and distance as independent variables. Travel costs, income and age variables do not significantly affect the frequency of visits. The results obtained are that the economic benefits of the Geology Museum in 1 year are IDR 27,974,173,821.